PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPAS MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE NUMBERED HEAD TOGETHER (NHT) DI KELAS V SDN 19 BATU BULEK KECAMATAN LINTAU BUO UTARA KABUPATEN TANAH DATAR - Andini Sugiarti; Zuryanty (STKIP Subang, 2024)
This research aims to describe the improvement in science learning outcomes using the Numbered Head Together (NHT) type Cooperative Learning model in class V of SDN 19 Batu Bulek, North Lintau Buo District, Tanah Datar Regency. In this research, Classroom Action Research (PTK) is applied using qualitative and quantitative approaches. The subjects in this research were teachers (researchers) and 16 students consisting of 11 women and 5 men. The results of this research show an increase in: a) teaching modules in cycle I with an average of 85.4% (Good) and cycle II 91.6% (Very Good) b) implementation in the teacher aspect of cycle I with an average of 84.25 % (Good) and cycle II 93.7% (Very Good), while implementation in the student aspect of cycle I averaged 82.75% (Good) and cycle II 93.7% (Very Good) c) assessment of The students' improvement in learning outcomes in cycle I obtained 80% and cycle II with an average of 88.12%. Based on these results, it can be concluded that the Numbered Head Together (NHT) Cooperative Learning model can improve science and science learning outcomes in class V.